Discovery of a kilohertz quasi-periodic oscillation in 2S 0918‒549 - Jonker, Peter G. (2001)
We report the discovery of a kilohertz quasi-periodic oscillation (kHz QPO) in the low-mass X-ray binary (LMXB) 2S 0918-549. The kHz QPO has a frequency of 1156 ± 9 Hz, an FWHM of 70 ± 20 Hz, and a fractional rms amplitude of 18% ± 2%. We also detected for the first time a type I X-ray burst in this source. The compact object must therefore be a neutron star. Finally, we were able to classify the source as an atoll source exhibiting the full complement of spectral/timing states of this class (island and banana). From the peak burst flux, an upper limit on the persistent luminosity can be derived of 0.5% of the Eddington luminosity, making 2S 0918-549 one of the least luminous LMXBs showing a kHz QPO. We compare the fractional rms amplitudes of the upper kHz QPO across the ensemble of LMXBs. We find a strong anticorrelation with luminosity. In LMXBs with luminosities ∼ 100 times lower than those of Z sources, the fractional rms amplitude is a factor ∼ 10 larger.